Presidential Regulatory Competencies in the Brazilian Telecommunications Sector: Regulatory Policy, Republicanism and Public Interest Doctrine - Ribeiro, Cássio Lourenço (Law, State and Telecommunications Review, 2012)
This study examines the presidential competence to determine the legal regime for the provision of telecommunications services. The 1998 and 2008 General Delegations Plan ”“ PGO are discussed given that the partition of competencies acts as an institutional guarantee that open up spaces for individual participation in the formulation of public policies. This analysis focuses on the role of the President of Brazil in the process of enacting PGOs and to the institutional gaps generated therewith for civic virtue.